EFISIENSI TEKNIS DAN EFISIENSI PROFITABILITAS PERBANKAN SEBELUM DAN SETELAH KRISIS EKONOMI 2008 DENGAN MENGGUNAKAN METODE NON PARAMETRIK DATA ENVELOPMENT ANALYSIS (Studi pada Perbankan yang Terdaftar di BEI tahun 2006-2010) - Elvira, Finta; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2012)
Economic crisis in 2008 affected the entire world, including Indonesia. This crisis indirectly led to the decrease of profit and non-profit income and income before tax which are output variables of efficiency of the bank. The crisis also affected the availability of funds to the community, which in the end affects the cost of capital as the input variable of profitability efficiency. This study measures the technical and profitability efficiency of the banks which are listed on Indonesia Stock Exchange (IDX) over 2006-2010 before and after the 2008 economic crisis. This study used DEA (Data Envelopment Analysis) methods and ANOVA test. The results of hypothesis test with ANOVA test showed no difference in technical efficiency and profitability efficiency before and after the 2008 economic crisis. The result can give some suggestion to company or bank management regarding risk anticipation while crisis, Bank Indonesia regarding evaluation and application of policy on Bank industry, bank depositors, and inestors or shareholders of bank regarding information about bank performance while crisis.